Developing platform of 3-D visualization of forest landscape. (November 2022) - Yu, Heyuan; Wu, Mia M.; He, Hong S.
Abstract: The recording and simulation data of forest landscapes are massive, high-dimensional, and abstract, requiring intuitive representation. 3-D visualization is an efficient tool to comprehend possible landscape changes generated by real-world or forest landscape models. Based on current advantages of game engines (realism and convenience), we developed a platform for 3-D visualization of forest landscapes (FLV). FLV streamlines multiple software and programming languages to break barrier between geographic data and game engine and transforms outputs of forest landscape models into visualization parameters. Compared with previous 3-D visualizations, FLV has better realism, efficiency, and navigation. We used simulation data of post-volcanic eruption forest landscape recovery in Changbai Mountain as a case study and demonstrated functionalities of FLV. FLV can visualize seamlessly from individual tree to forest stand and landscape scales, and from individual year to decades and centuries temporal scales. It offers potential solutions for the digital representation of complex environmental change. Highlights: Development and application of a 3-D forest landscape visualization platform. The platform has high realism and efficiency, friendly interaction, and versatility. The platform has been applied to post-volcanic eruption forest landscape visualization. Provides an intuitive and stereoscopic visualization solution for the dynamics of the forest landscape in time and space.